(untitled) (Indian Journal of Animal Production and Management, 2015)
The “Bhilwara Zila Dugdh Utpadak Sahakari Sangh Limited” implemented the Rajasthan Women Dairy Project in the district in 1992. Two panchayat samities namely Asind and Shahpura were selected for the study as about 50 per cent (53 WDCS) were operating in the above two panchayat samities. Form each of the selected panchayat samities 12 WDCSs were randomly selected for the study constituting 24 WDCSs in all. The study included two categories of respondents i.e. women milk producers who were members of the cooperative society (member) and women milk producers who has not obtained the membership of women dairy cooperative society (non member). This non-member group of respondents served as the control group of the study. Majority of the respondents from both the groups were of middle age group ranging from 34-45 years, having superior educational status of members as compared to non members. The analysis of caste that majority of the respondents belonged to the backward caste category (O.B.C.), where as in case of non member upper caste were in majority. Majority of members (47.50%) possess 1-2 ha. where as non-members possessed land below 1 ha. categorized as marginal farmer. Majority (52.5%) of non members had low income i.e. below Rs. 20,000/- majority of members (37.5%) possessed above 6 milch animals where as majority of the non members (65.83%) possessed 1-2 milch animals. WDCS members had significant involvement in organizing all the four activities as compared to non-members.